The ghost next door - Stine, R. L. (New York : Scholastic, 1993)
Hannah is perplexed and unsettled when a strikingly pale boy suddenly appears to be living in the abandoned house next door.
4.8
5-8
580L
Keywords: Ghosts -- Fiction; Horror stories; Ghost stories; Horror fiction; Horror stories